Legal Liability of Start-Up Entrepreneurs Toward Consumers in Electronic Transactions - Putri Gemala Sari; Rinaldi; Madona, Era; Yulastri; Syafadilla, Yunike (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
AbstractThis study examines the legal responsibilities of start-up business operators toward consumers in electronic transactions within Indonesia’s rapidly expanding digital economy. Using a socio-legal qualitative approach that integrates document analysis, expert interviews, and case-based assessments, the research analyzes the extent to which platform practices align with Indonesia’s legal framework, including the Consumer Protection Law, the ITE Law, and data governance regulations. The findings reveal significant inconsistencies between the obligations mandated by law and the operational behavior of digital platforms, indicating that regulatory compliance remains superficial rather than substantive. Results show that start-up platforms often employ ambiguous Terms of Service, provide unclear information, and implement weak data protection mechanisms that fail to ensure meaningful consent or adequate security for consumer data. Dispute resolution systems are largely ineffective, characterized by slow responses, automated interactions, and opaque decision-making processes that prevent consumers from obtaining fair remedies. Furthermore, platforms frequently shift liability to sellers, logistics partners, or payment intermediaries, despite maintaining significant operational control through algorithms, payment facilitation, and marketplace governance.. Enforcement agencies face challenges in monitoring complex digital ecosystems, while legal frameworks remain insufficiently adaptive to platform-based business models. These conditions allow platforms to operate with minimal accountability, resulting in heightened consumer vulnerability. Overall, the study concludes that improving consumer protection in electronic transactions requires stronger regulatory oversight, standardized contractual transparency, enhanced data governance practices, and fair, accessible dispute resolution mechanisms. These reforms are essential to ensuring a more accountable, equitable, and secure digital marketplace in Indonesia. Keywords: Digital transactions; Start-up liability; Consumer protection; Data governance; Electronic commerce law.